2015
DOI: 10.1371/journal.pone.0131140
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Associations between Circulating T-Cadherin and High Molecular Weight-Adiponectin in Patients with Stable Coronary Artery Disease

Abstract: Close relationships exist between presence of adiponectin (APN) within vascular tissue and expression of T-cadherin (T-cad) on vascular cells. APN and T-cad are also present in the circulation but here their relationships are unknown. This study investigates associations between circulating levels of high molecular weight APN (HMW-APN) and T-cad in a population comprising 66 women and 181 men with angiographically proven stable coronary artery disease (CAD). Plasma HMW-APN and T-cad were measured by ELISA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Consistently, the vascular dysfunction and ischemia-induced heart problems have been observed in T-cadherin-deficient mice, similar to those of the adiponectindeficient mice [154,156,157]. In human, genetic polymorphisms of CDH13 are significantly associated with various cardiometabolic and vascular phenotypes [144,146,151,154,158,159].…”
Section: Receptors and Signaling Pathways Of Adiponectinsupporting
confidence: 58%
See 1 more Smart Citation
“…Consistently, the vascular dysfunction and ischemia-induced heart problems have been observed in T-cadherin-deficient mice, similar to those of the adiponectindeficient mice [154,156,157]. In human, genetic polymorphisms of CDH13 are significantly associated with various cardiometabolic and vascular phenotypes [144,146,151,154,158,159].…”
Section: Receptors and Signaling Pathways Of Adiponectinsupporting
confidence: 58%
“…It acts as an adiponectin receptor and binds to the hexamers and HMW multimers [143]. Due to the lacking of the transmembrane and intracellular domains, T-cadherin is considered to have no direct effects on adiponectin-mediated signal transduction in cells, but regulates the circulating levels and tissue distribution of this adipokine [144,145]. Genetic studies have shown that single nucleotide polymorphisms in CDH13, the gene encoding human T-cadherin, contribute to low levels of adiponectin [146 -151].…”
Section: Receptors and Signaling Pathways Of Adiponectinmentioning
confidence: 99%
“…Functional APN resistance was also demonstrated in the skeletal muscles of patients with chronic HF [49,50] as well as in the myocardium of patients with advanced HF, which regressed after LVAD implantation [41]. Considering the mutual relationship between circulating APN and tissue T-cad, it is plausible that T-cad negatively regulates the circulating levels of APN, inducing APN clearance from blood and sequestering it to the cardiovascular tissues [51]. The diminished expression of T-cad in patients with HF would lead to higher serum levels of APN and be a supplementary mechanism explaining the "adiponectin paradox" [23].…”
Section: Discussionmentioning
confidence: 99%
“…As such, sex and body composition parameters should be taken into account when exploring the association of circulating adiponectin with CVD. Of note, opposing gender-specific associations between circulating HMW adiponectin and circulating T-cadherin levels have been noted in patients with stable coronary artery disease [70]. Moreover, different genotypes of adiponectin could be associated with higher CVD risk in a gender-specific way, since data suggest that the C/C carriers of the rs266729 SNP of adiponectin may have increased CVD mortality risk compared to the C/G or G/G carriers in women, but not in men [71].…”
Section: Discussionmentioning
confidence: 99%